Identification of optimum stage of harvesting for seed yield and seed quality parameters of forage grasses - T, SUPRITHA C; KUMAR, VINOD (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at Indian Grassland and Fodder Research Institute, Southern Regional Research Station, Dharwad during kharif 2016 and laboratory studies in 2017 to identify the harvesting stages on seed yield and quality in guinea and brachiaria grasses. The experiment was laid out in simple RCBD with eight treatments replicated thrice. The results of the investigation revealed that treatment T8, i.e. seeds collected at 20 days after panicle emergence (DAPE) produced maximum number of panicles and number of racemes/panicle in guinea and brachiaria grasses, respectively. On the contrary, number of seeds/panicle were highest in treatment T1 (seeds harvested at 6 DAPE) in guinea grass and in treatment T6 in brachiaria grass. Likewise, the fresh weight of the seeds/panicle was highest in T1 in guinea grass and in T6 in brachiaria grass. Whereas, the treatment T5 (seeds harvested at 14 DAPE) in case of guinea grass and T6 (seeds harvested at 16 DAPE) in case of brachiaria produced maximum seed yield/panicle and ha, respectively. The treatment T8 recorded the highest germination percentage in guinea and brachiaria grasses, respectively. The same treatment also recorded the lowest dead seed per cent. The lowest seed germination (%) was recorded in T1 in both the crops. On the contrary, highest fresh un-germinated seeds was recorded in case of guinea grass seeds in T3 and in case of brachiaria seeds in T8. Higher vigour index was recorded in T8 (seeds harvested at 20 DAPE) in both the crops. Guinea grass can be harvested at 16 DAPE and brachiaria grass can be harvested at 18 DAPE to get maximum quantity of high quality seeds.